(untitled) (INNOVATIVE ECONOMY, 2025)
Bobrovnyk V.M., Andrushkevych Z.M. MICRO-MOMENTS IN THE DIGITAL TRANSFORMATION OF MARKETING: IMPACT ON THE CUSTOMER JOURNEY IN DIFFERENT BUSINESS MODELS Purpose. The aim of the article is to explore the practical aspects of the impact of short-term but meaningful interactions between a consumer and a brand in the digital environment, assess their role in shaping the customer journey in different business models, and generalize tools for measuring the effectiveness of such interactions in the context of modern marketing. Methodology of research. The study is based on an interdisciplinary approach that combines theoretical and practical aspects of analysing consumer behaviour in the digital environment in the context of the categories of “need” and “value”, and adapting marketing tools to the conditions of digital transformation. General scientific and specialized methods were used in the course of the research, which made it possible to comprehensively investigate micro-moments as a key factor in shaping the customer journey. To gain an in-depth understanding of current trends in the digital transformation of marketing, a review of current research was conducted, which allowed us to identify the most common practices of using micro-moments in marketing, identify gaps in theoretical and practical approaches to adapting marketing tools in the surrounding of digital change, and identify key aspects of using micro-moments in different contexts, including B2C, B2B, D2C, and C2C business models. This approach has provided a comprehensive understanding of the role of micro-moments in the modern marketing process, and allowed us to develop practical recommendations for brands on how to integrate micro-moments into their strategies in the context of digital marketing transformation. Findings. It has been proven that micro-moments are an important factor in shaping new brand interaction strategies with customers, and are formed at different stages of the customer journey. The key types of micro-moments and their connection with different stages of consumer decision-making were identified, which allows to accurately target marketing efforts at each stage of interaction. It was found that for the successful implementation of micro-moments in marketing strategies, it is necessary to better understand the needs and values of consumers, as well as to form a system of rapid brand response to changes in customer behaviour. The key aspects of the use of micro-moments in marketing strategies were identified. The key areas of measuring the effectiveness of interactions in different business models (B2C, B2B, D2C, C2C) were formed. Originality. The use of micro-moments in the context of digital marketing transformation and assessment of their impact on the formation of new consumer behaviour patterns characterized by nonlinearity and multi-vector nature was further developed. The practices of adapting marketing tools to the digital environment have been improved, allowing identifying micro-moments and using them to attract and retain customers in various business models. The main directions of influence of micro-moments on the formation of a personalized customer experience were substantiated, which, unlike the existing ones, determined their relationship with different stages of the customer journey in the context of four types of micro-moments and the effectiveness of interactions in different business models. Practical value. The results of the study contribute to improving communication processes with customers, optimizing the use of marketing resources, as well as creating competitive advantages and unique value propositions in various business models. The study can become an important resource for marketers, analysts, and digital communications professionals seeking to better understand consumer behaviour in the digital environment and effectively adapt marketing strategies to the conditions of digital transformation. It will also be useful for business managers and business owners interested in implementing innovative approaches to attract and retain customers, in particular through personalization of customer experience. Key words: micro-moments, digital transformation, customer journey, digital marketing, customer experience, personalization, business models, marketing strategies.